Management Audit as a Control Mechanism for Enhancing the Effectiveness of Human Resource Functions - Fitria Ananda; Idil Rakhmat Susanto; Ainun Arizah (Vifada Management and Social Sciences, 2024)
This study aims to examine the implementation of management audits as a control mechanism for evaluating the effectiveness of human resource (HR) functions within an organizational context. Using a qualitative research design with a descriptive approach, this study focuses on a case analysis conducted at a manufacturing company in Indonesia. The informants consisted of members of the top management team who were directly involved in strategic decision-making and human resource management. Data were collected through in-depth interviews, direct observation, and document analysis, utilizing primary data obtained from key informants to ensure data credibility and contextual accuracy. The findings reveal that, out of ten HR functions assessed, eight functions were implemented effectively, including recruitment, employee training and development, career planning and development, performance appraisal, compensation and rewards, industrial relations, occupational health and safety, and employee creativity development. However, two critical HR functions—human resource planning and employee selection and placement—were found to be inadequately implemented and lacked systematic procedures aligned with organizational needs. These deficiencies indicate potential risks to long-term workforce sustainability and organizational performance. This study highlights the strategic role of management audits in identifying strengths and weaknesses within HR functions and in supporting continuous organizational improvement. The findings contribute to the literature on management auditing and human resource governance by providing empirical evidence on how audit practices can enhance HR function effectiveness. Practically, the study offers managerial insights for organizations to strengthen HR governance and align HR strategies with business objectives to improve overall organizational effectiveness.